CORRELATION STUDY COVERAGE OF EXCLUSIVE BREASTFEEDING AND RISK FACTORS IN INDONESIA - Eny Qurniyawati; Fariani Syahrul (Universitas Airlangga, 2022)
Introduction: Exclusive breastfeeding decreases the possibility of death in newborns to achieve the 3rd SDGs goal. However, some provinces have not yet extended the quarry to include infants receiving exclusive breastfeeding. The research purposed to analyze the relationship in the middle of the inclusion of the fourth antenatal care, delivery in healthcare facilities, early commencement of breastfeeding, smoking mothers, and the inclusion of infants receiving exclusive breastfeeding. Methods: The study design was conducted using the correlation study from the 2019 Indonesian Health Profile and the 2020 Maternal and Child Health Profile. The unit of analysis was 34 provinces in Indonesia which were analyzed using scatter plot and Pearson correlation test. Result: The outcome of the scatter plot and correlation test manifested that the factors that correlated with the coverage of infants receiving exclusive breastfeeding were coverage of the fourth antenatal care (r=0.370), delivery in health care facilities (r=0.466), early initiation of breastfeeding (r=0.592), mother smoking (r=-0.608). Conclusion: It was concluded that the 4th antenatal care visit and parturition at a healthcare facility had a moderate and positive relationship. Early commencement of breastfeeding had a strong and positive relationship, while smoking mothers had a strong relationship with a negative direction. It was recommended that the government formulate special policies for regional targets with coverage of the fourth antenatal care, delivery in health care facilities, low early commencement of breastfeeding, and areas with a high percentage of smoking mothers. Keywords: exclusive breastfeeding, prenatal care, delivery obstetric, smoking, sustainable development